Bourke: Our Yarns The Stories Behind 'Blackfellas, Whitefellas' - Cowlishaw, Gillian (UTS ePRESS, 2006)
The stories and ideas from the Aboriginal people of Bourke, contained in this book, along with those of a few gubbas (whitefellas), are based on recordings made in the 1980s by Leatta Ballangary and Kevin Knight, and in the 1990s by John Mackay and Gillian Cowlishaw. The book highlights a small selection of what people said about their lives, each in their own style. The stories are presented as a history beginning from early memories of nineteenth century conditions.